Anode piece, electrochemical device and electronic device including said anode piece
The use of silicon-based particles with controlled porosity and silicon content in a negative electrode layer addresses the volume change issue in lithium-ion batteries, enhancing cycle life and energy density.
Patent Information
- Application Number
- JP2021533506
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-28
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2040-12-28
AI Technical Summary
Silicon-based materials for negative electrodes in lithium-ion batteries suffer from high volume change rates during lithium release, leading to structural breakdown and deterioration of electrochemical properties, affecting energy density, cycle life, and safety.
A negative electrode material layer composed of silicon-based particles and graphite particles with controlled porosity and silicon content, within specific ranges, to buffer volume expansion and maintain mechanical integrity.
Improves cycle characteristics, anti-expansion properties, and energy density of lithium-ion batteries by effectively managing silicon's volumetric expansion and maintaining structural stability.
Smart Images

Figure 0007620550000011 
Figure 0007620550000012 
Figure 0007620550000001
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of electrochemistry, and in particular to negative electrode strips, electrochemical devices and electronic devices including the negative electrode strips. [Background technology]
[0002] Lithium ion secondary batteries have advantages such as high energy storage density, high open circuit voltage, low self-discharge rate, long cycle life, excellent safety, etc., and are widely used in the fields of electric energy storage, mobile electronic devices, electric vehicles, aerospace equipment, etc. As mobile electronic devices and electric vehicles enter a stage of rapid development, the market demands for the energy density, safety, cycle characteristics, and service life of lithium ion secondary batteries are increasing.
[0003] Silicon-based materials have a theoretical capacity of 4200mAh / g, making them the currently known anode materials with the highest theoretical capacity, and silicon is abundant in storage and inexpensive, so the anode pieces in current lithium-ion batteries often use silicon-based materials as the next generation anode materials with high capacity per gram. However, during the lithium release process, the volume change rate of silicon-based materials is as high as 300% or more, making the anode materials easily broken and falling off, which affects the electrochemical properties of lithium-ion secondary batteries. Summary of the Invention
[0004] The present invention provides a negative electrode piece, an electrochemical device and an electronic device including the negative electrode piece, and aims to improve the electrochemical properties of the electrochemical device.
[0005] In the following, the present invention will be described using a lithium ion battery as an example of an electrochemical device, but the electrochemical device of the present invention is not limited to a lithium ion battery.
[0006] The specific technical proposals are as follows: In a first aspect of the present invention, there is provided an anode piece comprising an anode material layer including silicon-based particles and graphite particles, the silicon-based particles including silicon and carbon, a porosity α1 of the silicon-based particles and a silicon content B in the silicon-based particles satisfy P=0.5α1 / (B-α1B), 0.2≦P≦1.6, the porosity α1 of the silicon-based particles is 15%-60%, and the silicon content B in the silicon-based particles is 20wt%-60wt%.
[0007] In the present invention, the "porosity α1 of a silicon-based particle" refers to the percentage of the volume of the pores in the silicon-based particle relative to the total volume of the silicon-based particle.
[0008] In one embodiment of the present invention, the porosity α2 and silicon content B of the negative electrode piece satisfy P=0.5α2 / (B-α2B), 0.2≦P≦1.6. For example, the lower limit of P value can be any one of 0.2, 0.4, 0.5 and 0.8, and the upper limit of P value can be any one of 1.1, 1.5 and 1.6. If P value is less than 0.2, the pores left in the silicon-based particles are difficult to buffer the lithium insertion volume expansion of nanosilicon, and the mechanical strength of the carbonaceous material is difficult to withstand the large expansion stress, the structure of the silicon-based particles is destroyed, and the electrochemical properties are deteriorated. If P value is more than 1.6, the pores left in the silicon-based particles are too large, the mechanical compressive strength of the carbonaceous material is deteriorated, the silicon-based particles are easily destroyed during processing, and a large number of new interfaces are exposed, which deteriorates the initial efficiency and cycle properties, and reduces the energy density of the lithium-ion battery. Therefore, by controlling the P value within the above range, the energy density, cycle characteristics, and expansion prevention characteristics of the lithium ion battery can be effectively improved.
[0009] In the present invention, the porosity α1 of the silicon-based particles is 15% to 60%. For example, the lower limit of the porosity α1 of the silicon-based particles may be any one of 15%, 16%, 18%, 25%, 32% and 34%, and the upper limit of the porosity α1 of the silicon-based particles may be any one of 38%, 43%, 45%, 47%, 56% and 60%. If the porosity α1 of the silicon-based particles is less than 15%, the remaining space is difficult to buffer the lithium insertion volume expansion of the nanosilicon, and the mechanical strength of the carbonaceous material is difficult to withstand the huge expansion stress, the structure of the silicon-based particles is destroyed, and the electrochemical properties are deteriorated. If the porosity α1 of the silicon-based particles is more than 60%, the pores are too large, the compressive strength of the carbonaceous material is reduced, the silicon-based particles are easily destroyed during processing, and the electrochemical properties are deteriorated.
[0010] In the present invention, the silicon content B in the silicon-based particles is 20wt% to 60wt%. For example, the lower limit of the silicon content B may be any one of 20wt% and 40wt%, and the upper limit of the silicon content B may be any one of 45wt% and 60wt%. If the silicon content B is less than 20wt%, the capacity per gram of the negative electrode material layer is small. If the silicon content B is more than 60wt%, the volume change rate of the silicon-based particles upon lithium release becomes faster, more SEI is generated, and the consumption of lithium ions and electrolyte in the lithium ion battery becomes faster, which significantly increases the resistance of the lithium ion battery.
[0011] In the present invention, the silicon-based particles may contain silicon and carbon, and may further contain oxygen, nitrogen, phosphorus, sulfur, etc. In the present invention, the type of silicon-based particles is not particularly limited as long as the object of the present invention can be achieved, and may contain at least one type selected from, for example, nanosilicon, silicon nanosilicon, silicon carbon, nano silicon oxide, and silicon-metal alloy.
[0012] Overall, the anode piece provided by the present invention comprises an anode material layer comprising silicon-based particles and graphite particles. The silicon-based particles are provided with pores, and the porosity α1 of the silicon-based particles and the silicon content B of the silicon-based particles satisfy P=0.5α1 / (B-α1B), 0.2≦P≦1.6, so that the lithium insertion expansion of the silicon-based particles can be effectively alleviated, thereby improving the cycle characteristics and expansion deformation problem of lithium-ion batteries.
[0013] In one embodiment of the present invention, the porosity α2 of the negative electrode piece is 15% to 41%, for example, the lower limit of the porosity α2 of the negative electrode piece may be any one of 15%, 19% and 28%, and the upper limit of the porosity α2 of the negative electrode piece may be any one of 28%, 29%, 35% and 41%. If the porosity α2 of the negative electrode piece is less than 15%, the electrolyte is difficult to penetrate sufficiently, the transmission distance of lithium ions is increased, and the dynamics of the lithium ion battery is deteriorated. If the porosity α2 of the negative electrode piece is more than 41%, poor contact between the silicon-based particles and the graphite particles is likely to occur during the cycle of the lithium ion battery, the cycle characteristics are deteriorated, and the energy density of the lithium ion battery is reduced.
[0014] In the present invention, the "porosity α2 of the negative electrode piece" refers to the percentage of the volume of the pores between various particles in the negative electrode piece relative to the total volume of the negative electrode piece.
[0015] In the present invention, the pores in the silicon-based particles and the negative electrode pieces each independently include micropores with a pore size of less than 2 nm, mesopores with a pore size of 2 nm to 50 nm, or macropores with a pore size of more than 50 nm. In the present invention, the number of the micropores, mesopores, and macropores is not particularly limited as long as the object of the present invention can be realized.
[0016] In one embodiment of the present invention, the sum α of the porosity α1 of the silicon-based particles and the porosity α2 of the negative electrode piece satisfies 45%<α<90%. For example, the lower limit of the sum of the porosity α1 of the silicon-based particles and the porosity α2 of the negative electrode piece may be any one of 43%, 46%, 47%, 51%, 53%, 60%, 62% and 67%, and the upper limit of the sum of the porosity α1 of the silicon-based particles and the porosity α2 of the negative electrode piece may be any one of 71%, 72%, 73%, 88% and 89%. When the sum α of the porosity α2 of the negative electrode piece and the porosity α1 of the silicon-based particles is controlled within the above range, the cycle characteristics and expansion prevention characteristics of the lithium ion battery are significantly improved.
[0017] In one embodiment of the present invention, the content of silicon-based particles in the negative electrode material layer is 3wt% to 80wt%. For example, the lower limit of the content of silicon-based particles in the negative electrode material layer may be any one of 3wt%, 10wt%, 20wt%, 25wt%, 30wt%, 35wt% and 40wt%, and the upper limit of the content of silicon-based particles in the negative electrode material layer may be any one of 45wt%, 55wt%, 60wt%, 70wt% and 80wt%. When the content of silicon-based particles in the negative electrode material layer is controlled within the above range, the negative electrode material layer is maintained at a high capacity per gram, thereby improving the energy density of the lithium ion battery.
[0018] In the present invention, the content of the graphite particles in the negative electrode material layer is not particularly limited as long as the object of the present invention can be realized. For example, the content of the graphite particles in the negative electrode material layer may be 20wt% to 97wt%, the lower limit of the content of the graphite particles in the negative electrode material layer may be any one of 20wt%, 25wt%, 30wt% and 40wt%, and the upper limit of the content of the graphite particles in the negative electrode material layer may be any one of 50wt%, 60wt%, 70wt%, 80wt% and 90wt%. By controlling the content of the graphite particles in the negative electrode material layer within the above range, the conductivity of the negative electrode material layer is improved, the contact with the electrolyte is reduced, and the generation of SEI is reduced.
[0019] In one embodiment of the present invention, the peak intensity ratio of the D peak to the G peak in a Raman test of the silicon-based particles is 0.2 to 3. The D peak has a shift range of 1255 cm in the Raman spectrum of the silicon-based particles. -1 ~1355cm -1 The G peak has a shift range of 1575 cm in the Raman spectrum of silicon-based particles. -1 ~1600cm -1 When the peak intensity ratio of the D peak to the G peak in the Raman test of the silicon-based particles is controlled within the above range, the carbonaceous material of the silicon-based particles has sufficient pore defects, which is useful for suppressing expansion deformation during cycling, thereby improving the expansion prevention property and cycling property of the negative electrode piece.
[0020] In one embodiment of the present invention, there is a carbon material on the surface of the silicon-based particle, and the type of carbon material in the present invention is not particularly limited as long as the object of the present invention can be realized. For example, the carbon material may include at least one selected from amorphous carbon, carbon nanotubes, carbon nanoparticles, vapor-deposited carbon fibers, graphene, etc. In some embodiments of the present invention, the carbon nanotubes may include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes. In the present invention, the method for preparing the carbon material present on the surface of the silicon-based particle is not particularly limited as long as the object of the present invention can be realized. In the present invention, the content of the carbon material is not particularly limited as long as the object of the present invention can be realized. For example, it may be 0.01wt% to 1wt% with respect to the silicon-based particle, for example, 0.01wt%, 0.1wt%, 0.5wt% and 1wt%. The presence of a carbon material on the surface of the silicon-based particles is useful for improving the interfacial stability of the surface of the silicon-based particles, suppressing the deviation of the silicon-based particles, and effectively mitigating the structural destruction caused by the volume expansion of the silicon-based particles, thereby avoiding the generation of new interfaces, thereby improving the cycle characteristics and expansion deformation of the negative electrode pieces.
[0021] In one embodiment of the present invention, there is a polymeric material on the surface of the silicon-based particles, and the type of polymeric material is not particularly limited in the present invention, as long as the object of the present invention can be realized. For example, the polymeric material may include at least one selected from polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), polyvinylpyrrolidone (PVP), polyacrylic acid, polystyrene butadiene rubber, and derivatives thereof. In some embodiments of the present invention, the polymeric material may include sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinylidene fluoride, and sodium polyacrylate (PAANa). In the present invention, the preparation method of the polymeric material present on the surface of the silicon-based particles is not particularly limited, as long as the object of the present invention can be realized. In the present invention, the content of the polymeric material is not particularly limited, as long as the object of the present invention can be realized, and may be 0 wt% to 0.4 wt% with respect to the silicon-based particles, for example, 0 wt%, 0.025 wt%, 0.15 wt%, and 0.4 wt%.
[0022] In one embodiment of the present invention, the average particle size Dv50 of the silicon-based particles is less than 20 μm. If the average particle size Dv50 of the silicon-based particles exceeds 20 μm, problems such as scratches are likely to occur during processing of the negative electrode pieces, and the number of mutual contact points between the particles is reduced, which affects the cycle characteristics of the negative electrode pieces. By controlling the average particle size Dv50 of the silicon-based particles of the present invention to be within the above range, the cycle characteristics of the negative electrode pieces can be improved. In the present invention, the particle size of the graphite particles is not particularly limited, as long as the object of the present invention can be realized.
[0023] In one embodiment of the present invention, the silicon-based particles have a specific surface area of 50 m 2 / g. The specific surface area of the silicon-based particles is less than 50 m 2When the specific surface area of the silicon-based particles is larger than 1 / g, the side reaction affects the properties of the lithium ion battery, and a higher proportion of the binder needs to be consumed, which reduces the binding force between the negative electrode material layer and the negative electrode current collector, resulting in a high rate of increase in internal resistance. In the present invention, the specific surface area of the graphite particles is not particularly limited as long as the object of the present invention can be achieved.
[0024] The compressed density of the negative electrode piece of the present invention is 1.0 g / cm 3 ~1.9g / cm 3 This makes it possible to improve the energy density of the lithium-ion battery.
[0025] In the present invention, the negative electrode current collector contained in the negative electrode piece is not particularly limited, and may be any material that can achieve the object of the present invention, for example, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or composite current collector. In the present invention, the thickness of the negative electrode current collector and the negative electrode material layer is not particularly limited, and may be any material that can achieve the object of the present invention, for example, the thickness of the negative electrode current collector is 6 μm to 10 μm, and the thickness of the negative electrode material layer is 30 μm to 120 μm. In the present invention, the thickness of the negative electrode piece is not particularly limited, and may be any material that can achieve the object of the present invention, for example, the thickness of the negative electrode piece is 50 μm to 150 μm.
[0026] Optionally, the negative electrode piece may include a conductive layer located between the negative electrode current collector and the negative electrode material layer. The composition of the conductive layer is not particularly limited and may be any conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder.
[0027] The positive electrode piece of the present invention is not particularly limited, and may be any material that can achieve the object of the present invention. For example, the positive electrode piece usually includes a positive electrode collector and a positive electrode material layer. Here, the positive electrode collector is not particularly limited, and may be any material that can achieve the object of the present invention, for example, may include aluminum foil, aluminum alloy foil, or a composite current collector. The positive electrode material layer includes a positive electrode material, and the positive electrode material is not particularly limited, and may be any material that can achieve the object of the present invention, for example, may include at least one material selected from lithium nickel cobalt manganese oxide (811, 622, 523, 111), lithium nickel cobalt aluminate, lithium iron phosphate, lithium-rich manganese-based material, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate, and lithium titanate. In the present invention, the thickness of the positive electrode collector and the positive electrode material layer is not particularly limited, and may be any material that can achieve the object of the present invention. For example, the thickness of the positive electrode collector is 8 μm to 12 μm, and the thickness of the positive electrode material layer is 30 μm to 120 μm.
[0028] Optionally, the positive electrode piece may include a conductive layer located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited and may be any conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder.
[0029] The conductive agent is not particularly limited as long as the object of the present invention can be realized. For example, the conductive agent may include at least one selected from conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fiber, flake graphite, Ketjen black, graphene, etc. The binder is not particularly limited as long as the object of the present invention can be realized, and any binder known in the art may be used. For example, the binder may include at least one selected from polyacrylic alcohol, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyimide, polyamide-imide, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyvinylidene fluoride, polytetrafluoroethylene (PTFE), carboxymethyl cellulose, and sodium carboxymethyl cellulose (CMC-Na), etc. For example, styrene-butadiene rubber (SBR) is used as the binder.
[0030] In the present invention, the separator is not particularly limited as long as the object of the present invention can be realized. For example, the separator may be at least one selected from polyolefin (PO)-based separators mainly composed of polyethylene (PE) and polypropylene (PP); polyester films (e.g., polyethylene terephthalate (PET) films); cellulose films; polyimide films (PI); polyamide films (PA); spandex or aramid films; woven films; nonwoven films (nonwoven fabrics); microporous films; composite films; separator films; compressed films; spun films; and the like.
[0031] For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, a membrane, or a composite membrane having a porous structure, and the material of the substrate layer may include at least one selected from polyethylene, polypropylene, polyethylene terephthalate, polyimide, etc. Optionally, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or may be a mixed layer formed by mixing a polymer and an inorganic material.
[0032] For example, the inorganic layer includes inorganic particles and a binder, and the inorganic particles are not particularly limited and may be, for example, at least one selected from the group consisting of alumina, silica, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium oxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, barium sulfate, etc. The binder is not particularly limited and may be, for example, one or a combination of a plurality of materials selected from the group consisting of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene. The polymer layer includes a polymer, and the polymer material includes at least one selected from polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), etc. The lithium ion battery of the present invention further includes an electrolyte, and the electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolytic solution, and the electrolytic solution includes a lithium salt and a non-aqueous solvent.
[0033] In some embodiments of the present invention, the lithium salt may include at least one selected from LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate. For example, the lithium salt is LiPF6 because it provides high ionic conductivity and improves cycleability.
[0034] The non-aqueous solvent may be a carbonate ester compound, a carboxylate compound, an ether compound, another organic solvent, or a combination thereof. The carbonate ester compound may be a chain carbonate ester compound, a cyclic carbonate ester compound, a fluorocarbonate ester compound, or a combination thereof. Examples of the chain carbonate ester compound are dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), and combinations thereof. Examples of the cyclic carbonate ester compound are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), and combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, and combinations thereof. Examples of the carboxylic acid ester compounds are methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, gamma-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, and combinations thereof. Illustrative examples of such ether compounds are dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.Illustrative of the other organic solvents are dimethylsulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylmethylamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate salts and combinations thereof.
[0035] The present invention further provides an electrochemical device including the negative electrode piece according to any one of the above embodiments, the electrochemical device having excellent cycle characteristics, anti-expansion characteristics, rate characteristics and volumetric energy density.
[0036] The electrochemical device of the present invention is not particularly limited and may include any device in which an electrochemical reaction occurs. In some embodiments, the electrochemical device includes, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0037] The present invention further provides an electronic device including the electrochemical device according to the embodiment of the present invention, which has excellent cycle characteristics, expansion prevention characteristics, rate characteristics and volumetric energy density.
[0038] The electronic device of the present invention is not particularly limited and may be used in any electronic device known in the prior art. In some embodiments, the electronic device includes, but is not limited to, notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copiers, portable printers, stereo headsets, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, walkie-talkies, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, bicycle auxiliaries, bicycles, lighting equipment, toys, game consoles, clocks, power tools, flashlights, cameras, large household storage batteries, and lithium ion capacitors.
[0039] The preparation process of the electrochemical device is well known to those skilled in the art and is not particularly limited to the present invention. For example, the electrochemical device is manufactured by stacking the positive electrode pieces and the negative electrode pieces with a separator therebetween, wrapping or folding the stack as necessary, placing the stack in a case, injecting an electrolyte into the case, and sealing the case. In addition, an overcurrent protection element, a lead plate, etc. may be provided in the case as necessary to prevent pressure rise, overcharging and overdischarging, etc., inside the electrochemical device.
[0040] The negative electrode piece provided by the present invention, and the electrochemical device and electronic device comprising the negative electrode piece, comprises silicon-based particles and graphite particles in the negative electrode material layer of the negative electrode piece, and creates pores in the silicon-based particles, so that the porosity α1 of the silicon-based particles and the silicon content B in the silicon-based particles satisfy P=0.5α1 / (B-α1B), 0.2≦P≦1.6, thereby effectively mitigating the lithium insertion expansion of the silicon-based particles, and thereby improving the cycle characteristics and expansion deformation problems of the electrochemical device.
[0041] In order to more clearly explain the present invention and the prior art, the drawings used in the embodiments and the prior art are briefly described below. It is obvious that the following drawings are only some embodiments of the present invention. [Brief description of the drawings]
[0042] [Figure 1] FIG. 1 is a cross-sectional SEM (scanning electron microscope) view of a negative electrode piece according to one embodiment of the present invention. [Diagram 2] Figure 2 is an SEM image several times larger than that of Figure 1. Explanation of symbols: 10: pores in silicon-based particles; 20: pores in negative electrode pieces. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0043] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be described in more detail below with reference to the drawings and embodiments. It is clear that the described embodiments are only some of the embodiments of the present invention, and do not cover all of the embodiments. All other technical solutions obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.
[0044] In the embodiments of the present invention, the present invention will be described using a lithium ion battery as an example of an electrochemical device, but the electrochemical device of the present invention is not limited to a lithium ion battery.
[0045] FIG. 1 shows a cross-sectional SEM (scanning electron microscope) view of a negative electrode piece according to one embodiment of the present invention, and FIG. 2 is an SEM view enlarged several times from FIG. 1. Referring to FIG. 2, the pores 10 in the silicon-based particles are the pores inside the silicon-based particles, and the pores 20 in the negative electrode piece are the pores between various particles in the negative electrode material layer.
[0046] Working Example Hereinafter, the embodiments of the present invention will be described in more detail with reference to examples and comparative examples. Various tests and evaluations are performed as described below. In addition, "parts" and "%" are based on mass unless otherwise specified.
[0047] Measurement method and equipment: Porosity Measurement of Silicon-Based Particles: The interface of silicon-based particles is photographed with a scanning transmission electron microscope (STEM), and the porosity is measured using the obtained STEM image. Specifically, the STEM image is binarized using the image threshold using the software Image J. After adjusting the size according to the scale, the area of the pores is tallied using Analyze Particles, and the area ratio is obtained, which is the porosity α1 of the silicon-based particles. 20 or more silicon-based particles are randomly selected from the pole piece, and similar measurements are performed to obtain the average value.
[0048] Determination of silicon content in silicon-based particles: Silicon-based particles are sliced and average elemental mass percentages are measured using a linear scan of EDS (X-ray energy spectroscopy).
[0049] Porosity measurement of negative electrode strips: Using the same die, punch out 50 pieces of negative electrode pieces with a radius of d, measure the thickness h of each piece in ten-thousandths of a micrometer, place them in the sample compartment of an AccuPyc 1340 instrument, and measure the true volume V of the pole pieces using Bohr's law PV=nRT by filling the pole pieces in the sealed sample compartment with helium (He). After the measurement is completed, count the number of pieces and determine the apparent volume πd of the sample. 2 Calculate ×50×h. Finally, use the formula α2=1-V / πd 2 Calculate the porosity α2 of the negative electrode piece according to × 50 × h.
[0050] Specific surface area measurement: The amount of gas adsorbed onto the solid surface is measured at different relative pressures at constant temperature and low temperature (-199℃ to -193℃), and then the amount of adsorption of the sample monolayer is calculated based on the Brownauer-Emmett-Teller adsorption theory and its formula (BET formula), and the specific surface area of the solid is calculated. BET Official:
number
[0051] How to measure the capacity per gram of the anode material layer: Use a button battery to measure the capacity per gram of the negative electrode material layer. The assembled button battery is left in a constant temperature atmosphere of 25℃ for 5 minutes, discharged at 0.05C to 0.005V, left for 5 minutes, discharged at 20μA to 0.005V, the total capacity discharged in the two steps is D0, left for 5 minutes, charged at 0.1C to 2.0V, the charge capacity at this point is C0, and the initial charge efficiency is C0 / D0×100%.
[0052] Compressed density measurement of negative electrode pieces: A negative electrode piece with area S is punched out using a punching machine, its mass M1 is measured, and its thickness H1 is measured to the nearest ten thousandth of a micrometer. A similar punching machine is used to punch out a current collector of the same area S, its mass M2 is measured, and its thickness H2 is measured to the nearest ten thousandth of a micrometer. The compressed density of the negative electrode is (M1-M2) / (H1-H2) / S.
[0053] Particle size measurement: Approximately 0.02 g of powder sample is placed in a clean 50 ml beaker, approximately 20 ml of deionized water is added, and several drops of 1% surfactant are added to completely disperse the powder in water, and the powder is sonicated for 5 minutes in a 120 W ultrasonic cleaner, and the particle size distribution is measured using a laser particle size analyzer, MasterSizer 2000. Dv50 is the diameter at which the cumulative total is 50% in a volume-based distribution of particles as measured by a laser scattering particle size analyzer.
[0054] Powder material button cell test method: The negative electrode material obtained in the embodiment, conductive carbon black and binder PAA (modified polyacrylic acid) are put into deionized water in a mass ratio of 80:10:10, stirred to form a slurry, and coated with a doctor blade to form a coating with a thickness of 100 μm. After drying in a vacuum drying oven at about 85 ° C for 12 hours, cut into pieces with a diameter of 1 cm using a press in a dry environment, and assembled into a button battery in a glove box by using a metal lithium sheet as the counter electrode, a ceglard composite film as the separator, and adding an electrolyte. The charge and discharge measurement of the battery is performed using a LAND series battery tester to measure its charge and discharge capacity. First, discharge to 0.005 V at 0.05 C, leave for 5 minutes, discharge to 0.005 V at 50 μA, leave for another 5 minutes, and discharge to 0.005 V at 10 μA to obtain the initial lithium insertion capacity of the material, and then charge to 2 V at 0.1 C to obtain the initial lithium desorption capacity. Finally, the initial lithium desorption capacity relative to the initial lithium insertion capacity is determined as the initial efficiency of the material.
[0055] Cycle characteristic measurements: The measurement temperature is 25 / 45°C, and the battery is charged to 4.4V at a constant current of 0.7C, charged to 0.025C at a constant voltage, left for 5 minutes, and discharged to 3.0V at 0.5C. The capacity obtained at that step is the initial capacity, and cycle measurements are performed at 0.7C charge / 0.5C discharge, and a capacity decay curve is obtained using the ratio of the capacity at each step to the initial capacity. The number of cycles at 25°C until the capacity retention rate reaches 90% is defined as the room temperature cycle characteristic of the lithium-ion battery, and the number of cycles at 45°C until the capacity retention rate reaches 80% is defined as the high temperature cycle characteristic. The cycle numbers for the above two cases are compared to obtain the cycle characteristics of the material.
[0056] Discharge rate measurement: At 25°C, discharge to 3.0V at 0.2C, leave for 5 minutes, charge to 4.45V at 0.5C, charge to 0.05C at a constant voltage, leave for 5 minutes, adjust the discharge rate, and perform discharge measurements at 0.2C, 0.5C, 1C, 1.5C, and 2.0C to obtain the discharge capacity at each rate. Compare the capacity obtained at each rate with the capacity obtained at 0.2C, and compare the rate characteristics as the ratio of the capacity at 2C to the capacity at 0.2C.
[0057] Measurement of the expansion rate of a lithium-ion battery when fully charged: The thickness of a new lithium-ion battery when it is half-charged is measured using a spiral micrometer. When it reaches 400 cycles (cls), the lithium-ion battery is in a fully charged state. The thickness of the lithium-ion battery at this time is further measured using a spiral micrometer, and by comparing it with the thickness of a new lithium-ion battery at the initial half-charge, the full-charge expansion rate of the lithium-ion battery at this time can be obtained.
[0058] Energy Density Calculation: After charging the lithium-ion battery to 4.45V at 25℃, measure the length, width and height of the lithium-ion battery with a laser thickness gauge to obtain the volume (V) of the lithium-ion battery, and then discharge it to 3V at 0.2C to obtain the lithium-ion battery discharge capacity (C) and average voltage plateau (U), and calculate the volumetric energy density (ED) with the formula: ED=C×U / V.
[0059] Example 1 <Preparation of negative electrode material> A porous carbon material with a porosity of 38% was placed in a sealed reactor containing a silicon-containing gas, heated to 500°C, kept at that temperature for 4 hours, cooled, and then sieved and demagnetized to obtain silicon-based particles with a carbon content of 60 wt%, a silicon content B of 40 wt%, and a silicon-based particle porosity α1 of 16%.
[0060] <Preparation of negative electrode piece> The negative electrode material prepared above, graphite particles, and nano-conductive carbon black were mixed in a mass ratio of 30:66.5:3.5 to obtain a first mixture. The first mixture and binder PAA were added to deionized water in a mass ratio of 95:5 to prepare a slurry with a solid content of 45%, and stirred until uniform to obtain a first mixed slurry. The first mixed slurry was uniformly applied onto one surface of a copper foil serving as a negative electrode current collector with a thickness of 8 μm, and dried in dry air at 120° C. for 2 min to obtain a coating layer weight of 7.5 mg / cm 2 A negative electrode piece having a negative electrode material applied on one side thereof was obtained. By completing the above steps, the coating of one side of the negative electrode piece was completed. The above steps were then repeated on the other surface of the negative electrode piece to obtain a negative electrode piece having a negative electrode material applied on both sides thereof. After completing the code press, a negative electrode piece having a porosity α2 of 15% was obtained, and the electrode piece was cut into a size of 41 mm × 61 mm.
[0061] <Preparation of positive electrode piece> The positive electrode materials, lithium cobalt oxide (LiCoO2), conductive carbon black (Super P), and polyvinylidene fluoride (PVDF), were mixed in a weight ratio of 97.5:1.0:1.5, N-methylpyrrolidone (NMP) was added as a solvent, and a slurry with a solid content of 75% was prepared and stirred until it was uniform. The slurry was evenly applied to one surface of an aluminum foil, which is a positive electrode current collector with a thickness of 10 μm, and dried at 90 ° C., resulting in a positive electrode piece with a coating layer thickness of 110 μm. By completing the above steps, the coating of one side of the positive electrode piece was completed. Then, the above steps were repeated on the other surface of the positive electrode piece, and a positive electrode piece with positive electrode material applied on both sides was obtained. After the coating was completed, the electrode piece was cut into a size of 38 mm x 58 mm.
[0062] <Preparation of electrolyte> In a dry argon gas atmosphere, organic solvents ethylene carbonate (EO), ethyl methyl carbonate, and diethyl carbonate were mixed in a mass ratio of EC:EMC:DEC = 30:50:20 to obtain an organic solution. Lithium hexafluorophosphate, a lithium salt, was then dissolved in the organic solvent and mixed until uniform, yielding an electrolyte with a lithium salt concentration of 1.15 Mol / L.
[0063] <Preparation of separator> Alumina and polyvinylidene fluoride were mixed in a mass ratio of 90:10 and dissolved in deionized water to form a ceramic slurry with a solid content of 50%.The ceramic slurry was then uniformly coated on one side of a porous substrate (polyethylene, thickness 7 μm, average pore size 0.073 μm, porosity 26%) by microgravure coating, and after drying, a two-layer structure of a ceramic coat and a porous substrate was obtained, and the thickness of the ceramic coat was 50 μm. Polyvinylidene fluoride (PVDF) and polyacrylic ester were mixed in a mass ratio of 96:4 and dissolved in deionized water to form a polymer slurry with a solid content of 50%. The polymer slurry was then uniformly applied to both surfaces of the two-layer structure of the ceramic coat and the porous substrate by a microgravure coating method, and after drying, a separator was obtained, and the thickness of the single-layer coating layer made of the polymer slurry was 2 μm.
[0064] <Preparation of lithium-ion batteries> The positive electrode, separator, and negative electrode prepared above were stacked in order so that the separator would be interposed between the positive and negative electrodes to act as an insulator, and then wound up to obtain an electrode assembly. The electrode assembly was placed on an aluminum plastic film exterior, dried, and then poured with an electrolyte. The assembly was then vacuum packaged, left to stand, formed, shaped, and other processes to obtain a lithium-ion battery.
[0065] In Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, Example 12, Example 13, Example 14, Example 15, Example 16 and Example 17, the preparation steps of <Preparation of negative electrode material>, <Preparation of negative electrode piece>, <Preparation of positive electrode piece>, <Preparation of electrolyte>, <Preparation of separator> and <Preparation of lithium ion battery> are all similar to Example 1, and the changes of related preparation parameters are as shown in Table 1.
[0066] [Table 1]
[0067] Example 18 <Preparation of negative electrode material> 1) A porous carbon material with a porosity of 38% was placed in a sealed reactor containing a silicon-containing gas, heated to 500°C, kept at that temperature for 4 hours, cooled, and then sieved and demagnetized to obtain silicon-based particles with a carbon content of 60 wt%, a silicon content B of 40 wt%, and a silicon-based particle porosity α1 of 16%. 2) The silicon-based particles obtained in 1) were placed in single-walled carbon nanotubes (SCNT) containing a dispersant of sodium carboxymethylcellulose (CMC-Na), dispersed for 2 hours until a uniform mixed solution was obtained, and then spray-dried to obtain a powder. The powder was crushed and sieved through a 400 mesh to obtain the negative electrode material, where the mass ratio of silicon-based particles:SCNT:sodium carboxymethylcellulose was 99.75:0.1:0.15.
[0068] <Preparation of negative electrode piece>, <Preparation of positive electrode piece>, <Preparation of electrolyte>, <Preparation of separator>, and <Preparation of lithium ion battery> were the same as in Example 2.
[0069] In Example 19, Example 20, Example 21, Example 22, Example 23, Example 24, Example 25, Example 26, Example 27, Example 28, Example 29, Example 30, Example 31, Example 32 and Example 33, the preparation steps of <Preparation of negative electrode material>, <Preparation of negative electrode piece>, <Preparation of positive electrode piece>, <Preparation of electrolyte>, <Preparation of separator> and <Preparation of lithium ion battery> are all similar to those in Example 18, and the changes of related preparation parameters are as shown in Table 2.
[0070] [Table 2]
[0071] In Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Comparative Example 6, the preparation steps of <Preparation of negative electrode material>, <Preparation of negative electrode piece>, <Preparation of positive electrode piece>, <Preparation of electrolyte>, <Preparation of separator> and <Preparation of lithium ion battery> were all similar to those in Example 1, and the changes of related preparation parameters were as shown in Table 3.
[0072] [Table 3]
[0073] The preparation parameters of Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Comparative Example 1 and Comparative Example 2 were as shown in Table 4.
[0074] [Table 4]
[0075] The measurement results of Examples 1, 2, 3, 4, 5, 6, 7, Comparative Example 1, and Comparative Example 2 are shown in Table 5.
[0076] [Table 5]
[0077] The preparation parameters of Example 8, Example 9, Example 10, Example 11, Example 12, Example 13, Example 14, Example 15, Example 16, Example 17, Comparative Example 3, Comparative Example 4, Comparative Example 5, and Comparative Example 6 were as shown in Table 6.
[0078] [Table 6]
[0079] The measurement results of Examples 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, Comparative Example 3, Comparative Example 4, Comparative Example 5, and Comparative Example 6 are shown in Table 7.
[0080] [Table 7]
[0081] The preparation parameters of Example 2, Example 18, Example 19, Example 20, Example 21, Example 22, Example 23, Example 24, Example 25, Example 26, Example 27, Example 28, Example 29, Example 30, Example 31, Example 32, and Example 33 were as shown in Table 8.
[0082] [Table 8]
[0083] The measurement results of Examples 2, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, and 33 are shown in Table 9.
[0084] [Table 9]
[0085] From Example 1, Example 2, Example 3, Example 4, Example 5 and Comparative Example 1 and Comparative Example 2, it can be seen that when the silicon content B is constant, there is no significant difference in the capacity per gram of the negative electrode material layer, and with the increase in the porosity α1 of the silicon-based particles, the specific surface area of the silicon-based particles gradually increases. From Example 3, Example 6, and Example 7, it can be seen that the change in the silicon content B in the silicon-based particles brings about a change in the P value, which affects the capacity per gram of the negative electrode material layer and the specific surface area of the silicon-based particles.
[0086] From Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7 and Comparative Example 1 and Comparative Example 2, it can be seen that if the P value is too small, the pores left inside the silicon-based particles are difficult to buffer the lithium insertion volume expansion of nanosilicon, and at this time, the mechanical strength of the carbonaceous material is difficult to withstand the huge expansion stress, the structure of the silicon-based particles is destroyed, and the electrochemical properties of the lithium ion battery are deteriorated; if the P value is too large, the pores left inside the silicon-based particles are too large, not only the mechanical compressive strength of the carbonaceous material is deteriorated, but also the silicon-based particles are easily destroyed during processing, and a large number of new interfaces are exposed, which deteriorates the initial efficiency and cycle characteristics, and reduces the overall energy density of the lithium ion battery. If the P value is within the range limited by the present invention, the cycle characteristics, expansion prevention characteristics and volume energy density of the lithium ion battery can be effectively improved, and at this time, the silicon-based particles have a certain amount of space for the lithium insertion expansion of silicon, and can also achieve both the stability and processability of their structure.
[0087] From Example 8, Example 9, Example 10, Example 11, Example 12 and Comparative Example 3 and Comparative Example 4, it can be seen that when the porosity of silicon-based particles is constant, the porosity of the negative electrode piece is too low, and the cycle characteristics and expansion characteristics of the lithium ion battery are significantly deteriorated. This is because the pores inside the silicon-based particles cannot fully alleviate the volume expansion of silicon when lithium is inserted, and the porosity of the negative electrode piece needs to further alleviate the volume expansion of silicon when lithium is inserted. In addition, the volume expansion makes it difficult for the electrolyte to fully penetrate, and the transmission distance of lithium ions is increased, and the dynamics of the lithium ion battery is deteriorated. If the porosity of the negative electrode piece is too high, the gap between the particles of the negative electrode material layer is too large, the contact area between the particles is reduced, the insertion points of lithium ions are reduced, and the lithium ion battery is easily detached during the cycle, and the cycle characteristics, expansion prevention characteristics and dynamics of the lithium ion battery are significantly deteriorated, and the compression density of the negative electrode piece is reduced, and the volume energy density of the lithium ion battery is also significantly reduced.
[0088] From Example 13, Example 14, Example 15, Example 16, Example 17 and Comparative Example 7 and Comparative Example 8, it can be seen that when the porosity of the negative electrode piece is constant, the porosity of the silicon-based particles is too low, and the cycle characteristics and expansion characteristics of the lithium ion battery are significantly deteriorated. This is because the space left in the silicon-based particles is difficult to buffer the lithium insertion volume expansion of nanosilicon, and at this time, the mechanical strength of the carbonaceous material is difficult to withstand the huge expansion stress, and the structure of the silicon-based particles is easily destroyed during cycling. If the porosity of the silicon-based particles is too high, the compressive strength of the carbonaceous material is reduced, the silicon-based particles are easily destroyed during processing, the electrochemical properties are deteriorated, and the compressed density of the electrode piece is reduced, and the volumetric energy density of the lithium ion battery is also reduced.
[0089] From Examples 8, 9, 10, 11, 12, 13, 14, 15, 16 and 17, it can be seen that the porosity of the negative electrode piece in the lithium ion battery and the porosity of the silicon-based particles can be rationally combined to more effectively improve the cycle characteristics and expansion prevention characteristics of the lithium ion battery, and improve the volumetric energy density.
[0090] Comparing Examples 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, and 33 with Example 2, it can be seen that adding SCNT with a content of 0.1 wt% to the surface of silicon-based particles significantly improves the cycle characteristics, adding MCNT with a content of 0.1 wt% improves the cycle characteristics slightly, and adding SCNT with a content of 0.05 wt% and MCNT with a content of 0.05 wt% improves the cycle characteristics to a certain extent. From Examples 18, 21, 22, 23, and 24, in which the amount of SCNT added was changed, it was found that by controlling the amount of SCNT added to be ≦0.5%, the cycle characteristics could be effectively improved, but when the amount of SCNT added was 0.5 wt%, the improvement in cycle characteristics was not obvious compared to the amount of SCNT added of 0.1 wt%, and the initial efficiency was deteriorated instead; when the amount of SCNT added was 1 wt%, the slurry could not be processed due to the excessive SCNT. From Examples 18, 25, 26, and 27, in which different dispersants were compared, it was found that without adding a dispersant, the SCNT could not be dispersed, the effect was poor, and the cycle characteristics and deformation of the lithium-ion battery were deteriorated; when PVP and PVDF were used as dispersants, the cycle characteristics were slightly deteriorated compared to CMC-Na and PAANa. From Examples 18, 28, 29, and 30, in which the amount of dispersant added was changed, it was found that when the amount of dispersant was 0.4 wt%, the dispersion effect was improved, but when the amount of dispersant was too much, the rate characteristics were deteriorated, and when the amount of dispersant was 0.025 wt%, the dispersion effect was poor, and the cycle characteristics and rate characteristics were slightly deteriorated compared to when the content was 0.15 wt%. From Examples 28, 31, 32, and 33, in which the coating with different carbon materials was compared, the results showed that the coating effect of CNT and graphene was the best. This is because when the material was coated with CNT and graphene, not only the electronic conductivity of the material was improved, but also the contact points between the materials were increased, and the cycle attenuation due to poor contact was reduced.
[0091] To summarize the above analysis, it can be seen that the negative electrode piece provided by the present invention can significantly improve the cycle characteristics and the expansion deformation problem of the electrochemical device.
[0092] The above are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the present invention.
Claims
1. A negative electrode piece including a layer of a negative electrode material including silicon-based particles and graphite particles, the silicon-based particles include silicon and carbon; The porosity α of the silicon-based particles 1 and the silicon content B in the silicon-based particles is P=0.5α 1 / (B-α 1 B), 0.2≦P≦1.6 is satisfied; The porosity α of the silicon-based particles 1 is 15% to 60%, and the silicon content B in the silicon-based particles is 20 wt % to 60 wt %, The porosity α of the negative electrode piece 2 is 15% to 41%, The negative electrode piece has a compressed density of 1.57 g / cm 3 to 1.78 g / cm 3 .
2. The porosity α of the silicon-based particles 1 and the porosity α of the negative electrode piece 2 The negative electrode piece according to claim 1 , wherein the sum α of and satisfies 45%<α<90%.
3. 2. The negative electrode piece according to claim 1, wherein the content of silicon-based particles in the negative electrode material layer is 3 wt % to 80 wt %.
4. The silicon-based particles have a peak intensity ratio of a D peak to a G peak in a Raman test of 0.2 to 3; The D peak has a shift range of 1255 cm in the Raman spectrum of silicon-based particles. -1 ~1355cm -1 The G peak has a shift range of 1575 cm in the Raman spectrum of silicon-based particles. -1 ~1600cm -1 The negative electrode piece of claim 1 , wherein the peak is located at
5. 2. The anode piece of claim 1, wherein a carbon material is present on the surface of the silicon-based particles, the carbon material comprising at least one selected from amorphous carbon, carbon nanotubes, carbon nanoparticles, vapor-deposited carbon fibers, and graphene.
6. The negative electrode piece according to claim 1 , wherein the silicon-based particles have an average particle size Dv50 of less than 20 μm.
7. The specific surface area of the silicon-based particles is 50 m 2 2. The negative electrode piece of claim 1, wherein the anode piece has a surface area of less than 1 / g.
8. An electrochemical device comprising the negative electrode piece according to any one of claims 1 to 7.
9. An electronic device comprising the electrochemical device of claim 8.
Citation Information
Patent Citations
Silicon composite particle, production method of same, and negative electrode material for nonaqueous electrolyte secondary battery
JP2005310759A
Negative electrode for electric device and electric device using the same
JP2014241263A